2020
DOI: 10.1016/j.cmet.2020.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Hypoglycemia in Patients after Gastric Bypass Surgery Is Mediated by Glucose-Induced IL-1β

Abstract: Highlights d Post gastric bypass surgery, glucose-induced IL-1b triggers insulin and hypoglycemia d SGLT2-inhibition prevents glucose-induced IL-1b effects d SGLT2 or IL-1b inhibition prevents postprandial hypoglycemia after gastric bypass d Monocytes after gastric bypass surgery are in a hyperreactive inflammatory state

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 40 publications
0
27
2
1
Order By: Relevance
“…Third, we approached the patients in our clinic and the Hypo-BEAR trial participants (15) to collect in unstructured discussions with individual patients any potential patient-relevant outcome measures which we then presented to two of the most severely affected patients in our clinic with postprandial hypoglycemia (s. supplements, preliminary questionnaire) who agreed to support us for this project with their patient feedback. We expected that quality of life and hypoglycemia would be the most relevant outcome domains.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we approached the patients in our clinic and the Hypo-BEAR trial participants (15) to collect in unstructured discussions with individual patients any potential patient-relevant outcome measures which we then presented to two of the most severely affected patients in our clinic with postprandial hypoglycemia (s. supplements, preliminary questionnaire) who agreed to support us for this project with their patient feedback. We expected that quality of life and hypoglycemia would be the most relevant outcome domains.…”
Section: Methodsmentioning
confidence: 99%
“…A recent exploratory trial with 12 patients after gastric bypass indicated that both the SGLT2-inhibitor empagli ozin and the IL-1 receptor antagonist anakinra may reduce postprandial insulin release and prevents hypoglycemia (15). These ndings call for further evaluation in a larger randomized clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Treatment of individuals with PBH with an Il-1B antagonist increased nadir glucose during meal testing. 35 Whether aberrant inflammatory responses contribute more broadly to PBH will require additional study.…”
Section: Etiologymentioning
confidence: 99%
“…Elevated IL-1β leads to an exaggerated postprandial insulin release. [ 44 ] A previous study reported that β-cell mass also increased in patients with PRH. [ 45 ] However, another study was designed to reduce β-cell mass by partial pancreatectomy, but it had no effects on improving hypoglycemia in patients with PRH, which indicated that β-cell mass was not the dominant contributor to hypoglycemia.…”
Section: Currently Possible Mechanisms Underlying Prhmentioning
confidence: 99%